(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Accounting plays a vital role in today’s modern business. It is very much essential to maintain books of accounts for every business and to know its profitability and solvency position of the business. The purpose of this research is to determine the latest trends in accounting. This review focus on the maintenance of books of accounts is necessary for every company. Due to various factors, accountancy needs more research on accounting standards. Accounting professionals also play an important role in a present modern organizations. Role of accounting professionals affecting cash management, Budgetary control, cost management, and other factors in the achievement of their target among similar companies, etc.